2012
DOI: 10.1590/s0100-879x2012007500003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human immunodeficiency virus type 1 subtypes in the state of Amazonas, Brazil, and subtype C identification

Abstract: Few studies have reported the molecular epidemiological characterization of HIV-1 in the Northern region of Brazil. The present study reports the molecular and epidemiological characterization of 31 HIV-1 isolates from blood donors from the State of Amazonas who donated blood between April 2006 and March 2007. Serum/plasma samples from all donors were screened for HIV antibodies by ELISA and the results confirmed by Western blot analysis. Genomic DNA was extracted from the buffy coat using the Super Quik-Gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
5
14
0
Order By: Relevance
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 93%
“…This was consistent with other data from Brazil [12][13][14][15][16][17][18][19][20] with the exception of the southern states, where subtype C has been found to prevail. 21 To a lesser extent, presence of recombinant forms between subtypes B and F, K and between F and subtype F1 was also found.…”
Section: Discussionsupporting
confidence: 93%
“…Subtype B was also highly prevalent in Pará state representing 97% of 34 protease sequences of pregnant women [25] and 85% in patients failing HAART [22]. A previous study in 31 HIV-1 sequences of blood donors from Amazonas also showed the predominance of subtype B [21] and a recent study in 129 antiretroviral naïve children from Manaus showed 80.2% subtype B infections [27]. Only subtype B was identified in Boa Vista, the capital of Roraima, the northern most Brazilian state, which is only connected by road to Amazonas state, Venezuela and Guyana.…”
Section: Discussionmentioning
confidence: 99%
“…HIV contains two long terminal repeats (LTR) at the end of its genome that include cis-regulatory sequences important for the expression of the provirus. In addition, at least nine protein-coding genes are distributed between the LTRs, including three structural proteins (Gag, Pol, and Env), two regulatory proteins (Tat and Rev), and four accessory proteins (Vif, Vpr, Vpu, and Nef) (Sides et al, 2005;Cunha et al, 2012). Whole-genome sequencing of HIV facilitates the identification of HIV subtypes, and this strategy is considered the gold standard for HIV classification (Robertson et al, 2000).…”
Section: Infection With Human Immunodeficiency Virus (Hiv) Typically mentioning
confidence: 99%
“…This pattern was supported by the datasets derived from sequencing of Env and Gag/Env, which revealed that Gag/Env accounted for the highest gene diversity among all markers tested. This may be explained by the relative mutation rates of Gag and Env, which encode two of the three core structural proteins of HIV (the core protein and the envelop protein, respectively) (Sides et al, 2005;Cunha et al, 2012). However, these two genes have distinct mutation rates.…”
Section: Statistical Index Of Different Markers On Identifying Hivmentioning
confidence: 99%